Financial Institution In Agriculture Finance: Enhancing Role And Impact On Farmer’s Income (Journal of Namibian Studies : History Politics Culture, 2023)
Agricultural financing is an essential element of agricultural development activities that attempt to enhance productivity. Adequate and prompt finance is essential for farmers to obtain the necessary resources for irrigation, farm mechanization, and land development. The study aims to reviews the role of agriculture finance and its impact on farmer's income, with a focus on analyzing the role of financial institutions and exploring factors that enhance farmer's income and productivity. The researcher employed a descriptive and analytical approach, utilizing both quantitative and qualitative methods. Primary data was collected through surveys/questionnaires distributed among 50 randomly selected farmers with an understanding of agriculture finance and the role of financial institutions. Secondary data was gathered through a review of existing literature related to the topic.The findings provide insights into the significance of financial institutions in agriculture and identify factors that contribute to enhancing farmer's income and productivity, thereby informing targeted policies and interventions in the agricultural sector.